PENERAPAN KONSEP CO LIVING PERMACULTURE DALAM REDESAIN RUSUN HARUM TEBET - Brian Putra Jiu; Priscilla Epifania Ariaji (Jurusan Arsitektur dan Perencanaan, 2026)
The Tebet subdistrict is a densely populated residential area with a population density of 20,000 people per km², driving high demand for vertical housing. The Harum Tebet public housing complex, established in 1997 for low-income communities, now faces challenges in the form of building degradation, minimal communal spaces that create isolation, and a lack of green areas. This study aims to redesign the flats by responding to the lack of effective space to increase social interaction and green open space (RTH) through a conceptual approach of Co-Living and permaculture. The research method uses surveys and observations to identify residents' needs. The analysis results show that the site has significant open space potential that can be converted into a productive landscape. This allows for the implementation of vertical farming, communal gardens, and composting and rainwater management systems without drastic structural changes. This redesign is expected to create an eco-communal housing model that improves space quality, social interaction, and environmental sustainability, thereby setting a relevant precedent for the revitalization of other similar flats. Keywords: Co-Living; communal space; permaculture; public housing; regenerative architecture Abstrak Kecamatan Tebet merupakan kawasan residensial padat dengan tingkat kepadatan mencapai 20.000 jiwa per km² , mendorong tingginya permintaan hunian vertikal. Rusunawa Harum Tebet, didirikan pada tahun 1997 untuk Masyarakat Berpenghasilan Rendah (MBR) , kini menghadapi tantangan berupa degradasi bangunan , ruang komunal minim yang menciptakan keterasingan , serta kurangnya area hijau. Studi ini bertujuan untuk meredesain rusun dengan merespons kurangnya efektivitas ruang untuk meningkatkan interaksi sosial serta Ruang Terbuka Hijau (RTH) melalui pendekatan konseptual Co-Living dan permakultur. Metode penelitian menggunakan survei dan observasi untuk mengidentifikasi kebutuhan warga. Hasil analisis menunjukkan bahwa tapak memiliki potensi ruang terbuka signifikan yang dapat diubah menjadi lanskap produktif. Hal ini memungkinkan implementasi vertical farming, kebun komunal, dan sistem pengelolaan kompos serta air hujan tanpa perubahan struktur drastis. Redesain ini diharapkan dapat menciptakan model hunian eko-komunal yang meningkatkan kualitas ruang, interaksi sosial, dan keberlanjutan lingkungan , sehingga dapat menjadi preseden relevan untuk revitalisasi rusun serupa lainnya.